Pengaruh Upward Social Comparison di Instagram terhadap Tekanan Pencapaian pada Mahasiswa - Edgina Aisha Fawnia; Hilma Aulia; Samirana Putri Hauri; Tara Tabinda Galih; Khansa Najla Nadhifah (Jurnal Intelek Insan Cendikia, 2026)
Rapid technological advancements have influenced numerous dimensions of human existence. One of these is the rise of social media. Social media is used to share daily activities, and many individuals frequently experience to showcase their personal achievements. This often turns social media into a platform for showing off accomplishments. Consequently, it frequently leads to unrealistic expectations among students regarding their own performance. These unrealistic expectations often result in performance pressure for students.